Study of antibiotic prescription pattern in PICU of a tertiary care hospital - Bamel, Vivek Virbhan; Shahani, Savita Ramesh (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Infectious disease is one of the importance causes of mortality and morbidity in India, therefore pattern of use of antibiotics requires separate study as they differ from adult, Therefore the aim of our study is to observe the antibiotic prescription in the tertiary care hospital. Methods: A prospective observational study was carried out in the children admitted in PICU. The study was started after obtaining the approval from Institutional Ethics Committee. Written informed consent was obtained from a parent or legal guardian of participants. Results: There were 50 patients were enrolled. The maximum antibiotics were prescribed from cephalosporin class (42; 40.38%) which included ceftriaxone, cefixime, cefotaxim, cefpodoxime. The majority of cephalosporins were prescribed in miscellaneous cases followed by respiratory tract infections, gastrointestinal tract, Central nervous tract infections and nil in CVS cases, secondly higher number of antibiotics prescribed was metronidazole and from Aminopenicillin class which includes amoxiclav and ampicillin and another beta lactamase which includes ureidopenicilin and carbepenem. The majority of aminopenicillin were prescribed in miscellaneous group infections followed by respiratory tract infections. Conclusions: From this study, it can conclude that commonly antibiotic were from 3rd generation cephalosporins followed by metronidazole and other β lactamase inhibitor and all of the antibiotics were prescribed as per the national guidelines.